Influence on the stability of bioflavonoids cataractogenic effect of the lens for the light energy in the experiment (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Relevance of the project is to study the influence of flavonoids during the treatment of age-related cataracts.Purpose: study the effect bioflavonoids biophysical properties of lens components and the activity of antioxidant enzymes in the light exposure energy in the experiment.Methods. Experiments were performed in vitro. The first group was the control without irradiation. Second — no irradiation + quercetin, the third — the test samples — light exposure, the fourth — the use of light exposure and quercetin. In homogenates of lenses and chamber determination of moisture produced superoxide dismutase, catalase and glutathione peroxidase.Results: flavonoid quercetin has a strong protective effect on lenticular components with light effects in vitro. Under these conditions, the light scattering performance, light absorption and fluorescence increases to a lesser extent compared with irradiated control — average by 18 %, 15 %, 16.8 % respectively. Photo-inactivation of antioxidant enzymes in the presence of the lens of physiological concentrations of quercetin significantly less for glutathione — 36 % for catalase — by 31.9 %, for superoxide dismutase — by 48.1 %.Conclusions. In experimental studies found that flavonoid — Quercetin an appreciable extent has a protective effect against the damaging effect of light energy on the optical properties of lens components.
Keywords: age-related cataract; lens; antioxidant system; biophysical properties; flavonoids; experiment; in vitro